Association of Lower Spiritual Well-Being, Social Support, Self-Esteem, Subjective Well-Being, Optimism and Hope Scores With Mild Cognitive Impairment and Mild Dementia - dos Santos, Sabrina B.; Rocha, Gabrielli P.; Fernandez, Liana L.; de Padua, Analuiza C.; Reppold, Caroline T. (Frontiers in Psychology, 2018)
INTRODUCTION: Positive Psychology (PP) constructs contribute significantly to a better quality of life for people with various diseases. There are still few studies that have evaluated the evolution of these aspects during the progression of dementia. OBJECTIVE: To compare the scores for self-esteem, life satisfaction, affect, spirituality, hope, optimism and perceived support network between elderly people with mild cognitive impairment, mild dementia and moderate dementia and control group. METHODS: Cross-sectional study. The sample consisted of 66 healthy controls, 15 elderly people with mild cognitive impairment (MCI), 25 with mild dementia and 22 with moderate dementia matched by age, gender and schooling. The instruments used were: Spirituality Self Rating Scale, Rosenberg Self-Esteem Scale, Medical Outcomes Study’s Social Support Scale, Life Satisfaction Scale, Positive and Negative Affect Schedule, Revised Life Orientation Test and Adult Dispositional Hope Scale. RESULTS: The scores for spiritual well-being, social support, self-esteem, life satisfaction, positive affect, optimism, negative affect and hope differed significantly between the groups (p <0.05). The individuals with MCI and mild dementia had lower spiritual well-being, social support, self-esteem, life satisfaction, positive affect, optimism and hope scores and higher negative affect scores compared with the controls. The scores for PP constructs did not differ between the group of people with moderate dementia and the control group. CONCLUSION: Dementia was found to impact several PP constructs in the early stages of the disease. For individuals with greater cognitive impairment, anosognosia appears to suppress the disease’s impact on these constructs.